Glaucoma drainage devices implantation in uveitic glaucoma: a systematic review - Ardelia Emily; Novanita Shirley Satolom; Franky Richard Kasih; Kevin Kevin; Bobby Kristianto (DiscoverSys Inc., 2021)
Background: Uveitis is broadly defined as inflammation of the uvea. Glaucoma is the third most common complication of uveitis. Uveitic Glaucoma (UG) is known to be refractory, and multiple surgeries are often required for proper treatment. The purpose of this study is to determine the effectiveness of Glaucoma Drainage Device (GDD) implantation as a surgical procedure in UG patients.Method: We conducted a systematic search of electronic databases from PubMed, Science Direct, and SpringerLink using a combination of relevant keywords was performed by 5 independent reviewers. Various search terms, including 'glaucoma drainage device', 'glaucoma drainage implants', 'glaucoma filtration implants', 'aqueous shunts', 'uveitic glaucoma', 'inflammatory glaucoma'.Result: A total of 143 articles were retrieved, but only 14 articles were eligible for data extraction. There are 631 eyes from 583 patients who had UG, 442 eyes underwent GDD implantation. Overall, intraocular pressure and the use of glaucoma medication were reduced. Mean IOP preoperative is 31.57 mmHg, and IOP postoperative is 14.48 mmHg. There is a reduction in IOP of an average of 17.09 mmHg. The number of glaucoma medications has decreased from 3.24 to 1.29 postoperatively.Conclusion: UG has been shown to be managed successfully by GDD implantation. GDD implantation may be considered a long-term effective surgical option for patients with UG.